JURNALISME SASTRA: LAPORAN PERISTIWA SECARA NARATIF DAN VARIATIF - Suhaimi Suhaimi (Komunika, 2015)
Internet as a form of communication technology today, on the one hand has urged members of the press who worked on several major news papers to change form into smaller, but the number of pages grew thicker with a more slender appearance and full color. It is achallenge for reporters now are required to be more skilled from their elders in preparing the report journalism. Literary journalism or narrative reporting is news writing made in narra-tive form of variety of different angles according to the facts and not fiction essay. In Indonesia literary journalism gives a place for journalists to actualize his being. Therefore, it requires a journalist to be able to create a narrative, descriptive or a detailed, lively, contextual, and relevant reports